PENINGKATAN KEMAMPUAN BERBICARA (SPEAKING) BAHASA INGGRIS SISWA KELAS VIII SMPN 1 RANAH PESISIR DENGAN MENGGUNAKAN GAMBAR - Jamin, Antoni; Sari, Tiara Indah; Yani, Titik Hardewi; Yanto, Andri (STKIP Pesisir Selatan, 2025)
Speaking skills are one of the keys to a smooth life. Through speaking, people can quickly obtain the information they need, both near and far. These skills include reading, listening, speaking, and writing. This research aims to improve the quality of English learning at SMPN 1 Ranah Pesisir, especially students' speaking skills. This classroom action research is a comparative descriptive research, which describes the comparison of the learning process in the initial conditions, actions, and final conditions after the actions. This research was conducted in two cycles, namely Cycle I and Cycle II. The difference between the two cycles lies in the theme of the pictures used according to the learning material. The results of the study indicate that the use of picture media can improve students' ability to speak English. Interesting picture media also motivates students in class learning, students become interested in speaking English with their partners. They are not afraid to make mistakes in speaking English, and this makes them braver to speak in front of other friends or in front of the class. Of course, this is very positive in growing their confidence in mastering English speaking skills.